2008
DOI: 10.1136/emj.2008.059683
|View full text |Cite
|
Sign up to set email alerts
|

Cuffed oropharyngeal airway (COPA) placement is delayed by wearing antichemical protective gear

Abstract: Antichemical protective gear slowed proper placement of COPA and its fixation compared with surgical attire. COPA may be a temporarily useful device in non-conventional settings, but functional reassessment is required when injured patients reach medical facilities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 23 publications
1
10
0
Order By: Relevance
“…The results are in accordance with previous studies, which demonstrated that wearing C-PPE significantly prolongs the time to AW control while using ETI [11,12], SAD [26][27][28], and ETI aids [29]. However, most of these studies were done on a small samples [11,12,26], were limited to anesthesiologists or paramedics [11,12,25,28,29], or did not compare ETI with SADs [12,[26][27][28]. None of these studies compared second-generation SADs with ETI and first-generation SADs in these groups of medical caregivers.…”
Section: Discussionsupporting
confidence: 93%
“…The results are in accordance with previous studies, which demonstrated that wearing C-PPE significantly prolongs the time to AW control while using ETI [11,12], SAD [26][27][28], and ETI aids [29]. However, most of these studies were done on a small samples [11,12,26], were limited to anesthesiologists or paramedics [11,12,25,28,29], or did not compare ETI with SADs [12,[26][27][28]. None of these studies compared second-generation SADs with ETI and first-generation SADs in these groups of medical caregivers.…”
Section: Discussionsupporting
confidence: 93%
“…Despite there being numerous supraglottic airways [12], to date, only the LMA [7,9], the intubating LMA TM (LMA Company, Jersey, Channel Isles, UK) [13] and the cuffed oropharyngeal airway (COPA; Mallinckrodt Medical, Athlone, Ireland) [14] have been evaluated for use whilst wearing CBRN-PPE. Recently, however, Barns et al [15] evaluated the Laryngeal Tube TM (VBM Medizintechnik GmbH, Sulz, Germany) for use whilst wearing fire rescue equipment, but not specifically CBRN-PPE.…”
mentioning
confidence: 99%
“…performed all over the world, the United Kingdom (10), [19][20][21][22][23][24][25][26][27][28] Israel (6), [29][30][31][32][33][34] and the United States (5) 15,[35][36][37][38][52][53][54] ,published the majority of the studies. Australia (3), [39][40][41] South Africa (2), 42,43 Canada (1), 44 France (1), 45 and South Korea (1) 46 published the rest.…”
Section: Cbrn-ppe Effects On Medical Device Use During Emergency Respmentioning
confidence: 99%
“…Each study reported significant negative impacts on task completion times. Seven studies assessed IO 15,23,[29][30][31]35,45 , infusion, 6 evaluated IV 15,20,21,23,34,44 , drug administration, and 3 studies included subcutaneous drug administration. 19,42,44 , Many of the reviewed studies showed that peripheral IV catheter insertion is often difficult, resulting in more frequent failures (12% compared with 3% of IO), with an average increase in completion time of 90 s compared with IO.…”
Section: Taxonomy Of Ppe Impact On Device Use Impact On the Administrmentioning
confidence: 99%